Strategy and management, the foundations of any successful brand - Mayorga Escalada, Santiago (2019)
When analyzing any branding work we tend to simplify a process that by its nature is enormously complex and multidisciplinary. There is an important current of opinion that tends to reduce the creation of a brand to its logo or to the group of elements that will articulate the visual identity in a sort of cosmetic image, or purely aesthetic. Either by understanding branding as a superficial expense and not as a strategic investment, due to ignorance of the discipline, short-sightedness, lack of means and / or professionals or, by a mixture of all these factors, the brands themselves devalue in many cases from the moment they make the decision not to face their construction in a studied way, serious and coherent.